A framework addressing a safe ageing management in complex industrial sites: The Italian experience in «Seveso» establishments. (March 2019) - Milazzo, Maria Francesca; Bragatto, Paolo
Abstract: In Europe, the Directive 2012/18/EU (Seveso III) strengthens the obligation to adopt a program assuring the integrity of critical equipment at major hazard establishments, by taking into account actual deterioration mechanisms (internal and external corrosion, erosion, thermal and mechanical fatigue, etc.). The program must cover all phases of the lifecycle and ensure a safe ageing of equipment, particularly when these are reaching the final stage of life. The effectiveness of the integrity program must be carefully assessed during the audits planned by the establishment's operator as well as by inspectors on behalf of the Competent Authorities. The adoption of a Risk Based Inspection scheme provides a valuable help to face this matter. The operator is, anyway, required a considerable effort to face at least three issues related to: (i) the understanding of concurring physical and chemical phenomena; (ii) the management of information associated with each individual component and its history, (iii) the appropriate measurement, including acquisition and management of data. There is a considerable difficulty in understanding these issues during Seveso inspections and external audits, because time and resources are often limited. For this reason, models and methods supporting the definition of the ageing status and trend in industrial sites are needed. This paper analyses the main factors affecting ageing. A framework for "ageing" assessment in complex industrial sites, including "Seveso" establishments, is proposed; then, its validation, by means of data collected during a testing phase carried out in Italy, is also given. Highlights: Previous reports identified damage mechanisms as a significant cause of major accidents. In Europe, most industrial equipment is reaching the design lifetime. A model supporting the definition of the ageing status of equipment has been developed.